Minimal-access retroperitoneal pancreatic necrosectomy for infected necrotizing pancreatitis: a multicentre study of a step-up approach. Issue 10 (25th May 2020) - Liu, Z-W; Yang, S-Z; Wang, P-F; Feng, J; He, L; Du, J-D; Xiao, Y-Y; Jiao, H-B; Zhou, F-H; Song, Q; Zhou, M-T; Xin, X-L; et al.
Abstract: Background: Various minimally invasive approaches have been described for infected necrotizing pancreatitis. This article describes a modified minimal-access retroperitoneal pancreatic necrosectomy (MARPN) procedure assisted by gas insufflation. Methods: This retrospective, observational study documented patients who had undergone a step-up MARPN between 1 January 2010 and 31 December 2016. A minimum follow-up of 1 year was required for inclusion. The step-up approach involved percutaneous catheter drainage followed by the modified MARPN and necrosectomy. If more than one access site was needed it was categorized as complex MARPN. Results: Of 212 patients with infected necrotizing pancreatitis, 164 (77·4 per cent) underwent a step-up approach. The median number of percutaneous catheter drains and MARPN procedures was 3 (range 1–7) and 1 (1–6) respectively. Ninety patients (54·9 per cent) underwent complex MARPN. For residual necrosis after MARPN, three patients (1·8 per cent) underwent sinus tract gastroscopy, and 11 (6·7 per cent) had sinography combined with a tube change. However, operations in 13 patients (7·9 per cent) required conversion to open surgery. Postoperative complications developed in 103 patients (62·8 per cent). The mortality rate was 6·1 per cent (10 deaths). Conclusion: A step-up approach using a modified MARPN for infected necrotizing pancreatitis is a reasonable option. Graphical Abstract: Minimally invasive approaches have been used increasingly in the management of infected necrotizing pancreatitis. This study presents a modified minimal-access retroperitoneal pancreatic necrosectomy procedure assisted by carbon dioxide insufflation, instead of saline. A clear field of view without necrotic debris floating in saline makes the technique safe and efficient. High degree of successVIDEO Presented in part to the Joint Congress of the Sixth Biennial Congress of the Asian–Pacific Hepato-Pancreato-Biliary Association and the 29th Meeting of the Japanese Society of Hepato-Biliary-Pancreatic Surgery, Yokohama, Japan, June 2017